Chemical composition, antioxidant and antigenotoxic activities of different fractions of Gentiana asclepiadea L. roots extract - Mihailović, Vladimir; Matić, Sanja; Mišić, Danijela; Solujić, Slavica; Stanić, Snežana; Katanić, Jelena; Mladenović, Milan; Stanković, Nevena (Technische Universität Dortmund, 2013)
The aim of this study was to evaluate the antioxidant and antigenotoxic activities of chloroform, ethyl acetate and n-butanol fractions obtained from Gentiana asclepiadea L. roots methanolic extract. The main secondary metabolites sweroside, swertiamarin and gentiopicrine were quantified in G. asclepiadea root extracts using HPLC-DAD analysis. Amount of total phenols, flavonoids, flavonols and gallotannins was also determined. The antigenotoxic potential of extracts from roots of G. asclepiadea was assessed using the standard in vivo procedure for the detection of sex linked recessive lethal mutations in Drosophila melanogaster males treated with ethyl methanesulfonate (EMS). The results showed that the most abundant secoiridoid in G. asclepiadea roots was gentiopicrine and its content in the n-butanol fraction (442.89 mg/g) was the highest. Among all extracts, ethyl acetate fraction showed the highest antioxidant activity, as well as total phenolics (146.64 GAE/g), flavonoids (44.62 RUE/g), flavonols (22.71 RUE/g) and gallotannins (0.99 mg GAE/g) content. All the fractions showed antioxidant activity using in vitro model systems and the results have been correlated with total phenolics, flavonoids, flavonols and gallotannins content. In addition to antioxidant activity, G. asclepiadea root extract fractions possess an antigenotoxic effect against DNA damage induced by alkylation with EMS. The antioxidant activity exhibited by G. asclepiadea depended on the phenolic compounds content of the tested extracts, while there was no significant difference in the antigenotoxic potential between fractions.
EXCLI Journal ; Vol. 12, 2013
Keywords: antioxidant activity; antigenotoxicity; gentiopicrine; Gentiana asclepiadea L.; phenolic contents; secoiridoids; 610